Courses
Courses for Kids
Free study material
Offline Centres
More
Store

How do you differentiate $y=4\sqrt{x}$?

Last updated date: 05th Aug 2024
Total views: 387.9k
Views today: 4.87k
Verified
387.9k+ views
Hint: We explain the concept of derivation of a dependent variable with respect to an independent variable. We first find the formula for the derivation for ${{n}^{th}}$ power of a variable x where $\dfrac{d}{dx}\left( {{x}^{n}} \right)=n{{x}^{n-1}}$. We place the value for $n=\dfrac{1}{2}$. We get the solution for the derivative of $y=4\sqrt{x}$. We also explain the theorem with the help of the first order derivative.

Complete step by step answer:
Differentiation, the fundamental operations in calculus deals with the rate at which the dependent variable changes with respect to the independent variable. The measurement quantity of its rate of change is known as derivative or differential coefficients. We find the increment of those variable for small changes. We mathematically express as $\dfrac{dy}{dx}$ where $y=f\left( x \right)$.
The formula of derivation for ${{n}^{th}}$ power of a variable x is $\dfrac{d}{dx}\left( {{x}^{n}} \right)=n{{x}^{n-1}}$. The condition being $n\in \mathbb{R}\backslash \left\{ 0 \right\}$.
We know in case of indices we have the identity of $\sqrt[m]{a}={{a}^{\dfrac{1}{m}}}$.
For our given function $y=4\sqrt{x}$, we can convert it to $f\left( x \right)=4\sqrt{x}=4{{x}^{\dfrac{1}{2}}}$.
The value of n is $\dfrac{1}{2}$. We apply the theorem and get $\dfrac{df}{dx}=\dfrac{d}{dx}\left( 4{{x}^{\dfrac{1}{2}}} \right)=4\dfrac{d}{dx}\left( {{x}^{\dfrac{1}{2}}} \right)=4\left( \dfrac{1}{2} \right){{x}^{\dfrac{1}{2}-1}}$.
Simplifying the equation, we get $\dfrac{df}{dx}={{f}^{'}}\left( x \right)=2{{x}^{-\dfrac{1}{2}}}=\dfrac{2}{\sqrt{x}}$.

Therefore, the derivative of the function $y=4\sqrt{x}$ is $\dfrac{2}{\sqrt{x}}$.

Note: If the ratio of $\dfrac{\Delta y}{\Delta x}$ tends to a definite finite limit when $\Delta x\to 0$, then the limiting value obtained by this can also be found by first order derivative. We can also apply first order derivative theorem to get the differentiated value of ${{x}^{\dfrac{1}{2}}}$.
We know that $\dfrac{dy}{dx}=\underset{h\to 0}{\mathop{\lim }}\,\dfrac{f\left( x+h \right)-f\left( x \right)}{h}$. Here $f\left( x \right)={{x}^{n}}$. Also, $f\left( x+h \right)={{\left( x+h \right)}^{n}}$. We assume $x+h=u$ which gives $f\left( u \right)={{\left( u \right)}^{n}}$ and $h=u-x$. As $h\to 0$ we get $u\to x$.
So, $\dfrac{df}{dx}=\underset{h\to 0}{\mathop{\lim }}\,\dfrac{f\left( x+h \right)-f\left( x \right)}{h}=\underset{u\to x}{\mathop{\lim }}\,\dfrac{{{u}^{n}}-{{x}^{n}}}{u-x}$.
We know the limit value $\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{x}^{n}}-{{a}^{n}}}{x-a}=n{{a}^{n-1}}$.
Therefore, $\dfrac{df}{dx}=\underset{u\to x}{\mathop{\lim }}\,\dfrac{{{u}^{n}}-{{x}^{n}}}{u-x}=n{{x}^{n-1}}$.